STEM-16. DUAL INHIBITION OF PROTEIN ARGININE METHYLTRANSFERASE 5 AND PROTEIN PHOSPHATASE 2A ENHANCES THE ANTI-TUMOR EFFICACY IN PRIMARY GLIOBLASTOMA NEUROSPHERES. (11th November 2019) - Sur, Hannah; Gangaplara, Arunakumar; Wang, Xiang; Ray-Chaudhury, Abhik; Zhuang, Zhengping; Kumar, Sachin; Heiss, John; Young Yoo, Ji; Kaur, Balveen; Kumar Banasavadi-Siddegowda, Yeshavanth
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most common malignant primary brain tumor and has a heterogeneous tumor cell population. The median survival of GBM patients is less than two years with current multi-model therapy of maximal surgical resection followed by chemotherapy, radiation and tumor treating fields. Protein Arginine Methyltransferase 5 (PRMT5) regulates cellular functions through symmetric di-methylation of arginine residues of histone and non-histone proteins. Our recent findings show that PRMT5 is overexpressed in GBM; its inhibition causes apoptosis and senescence of mature and immature GBM tumor cells respectively. Protein Phosphatase 2A (PP2A), a serine-threonine phosphatase, is associated with senescent tumor cells that contribute to therapy resistance; LB100 is a first-in-class small molecule inhibitor of PP2A that can sensitize tumor cells that are chemo- and radiation-therapy resistant. In this study, using patient-derived primary GBM neurospheres (GBMNS), we tested the anti-GBM effect of concurrent PRMT5 and PP2A inhibition. METHODS: Patient-derived primary GBM neurospheres transfected with PRMT5 target-specific siRNA were treated with LB100 and subjected to in vitro assays such as proliferation assay, cell cycle analysis, cytotoxicity assay, PP2A activity and western blot. RESULTS: LB100 treatment significantly reduced the viability of PRMT5-depleted GBM cells as compared to PRMT5 intact cells. LB100 caused G1 cell cycle arrest through inactivation of Rb protein; this effect is further enhanced in combination with PRMT5-depletion. Combination therapy also increased the expression of phospho-MLKL; Necrostatin-1 rescued PRMT5-depleted cells from the cytotoxic effects of LB100 indicating that necroptosis caused the enhanced cytotoxicity in combination therapy. We also found that PRMT5-depletion increased the PP2A activity in GBM neurospheres. CONCLUSION: Combining the PRMT5 inhibition and PP2A inhibition produced greater antitumor effects than with PRMT5 inhibition alone.